The application of virtual laboratory as an effort to improve 10th grade students’ learning outcomes on environmental change topic - Raudlah Melinda Sidik; Suhara Suhara; Persitiwati Peristiwati (Assimilation: Indonesian Journal of Biology Education, 2022)
The purpose of this research was to identify the effect of a virtual laboratory application on the student results in the environmental changes topic at SMAN 16 Bandung. A virtual laboratory is an activity of learning with the use of software as a simulator containing all necessary equipment in preparation, tools, working step demonstration, and practicum observation. During the teaching and learning process, the teacher guided the students to understand the concept of learning, especially in the concept of environmental changes topic (pollution and climate changes). The students were directed to analyze and identify the problem of the topic itself, so they would develop the ability to think critically and solve the problems. The method used in this research was pre-experimental with a one-group pretest-posttest design. The sample in the research consisted of 34 students in one class experiment. Instruments used in this research consisted of 30 multiple choices questions with six options and a questionnaire about the attitude cases to the learning process. Supported research results showed that there was an effective effect in the application of virtual laboratory, with an N-gain value of 0.72 with the category of high effect. The average learning mastery of students after implementing a virtual laboratory was 88%. Learning outcomes about students' attitudes when learning using virtual laboratory showed a very good category with an average of 81%, with the highest attitude on indicators of collaboration and critical thinking.